The Significance of Swimming and Corrective Exercises in Water in Treatment of Postural Deficits and Scoliosis - Jerzy Eider; Wioletta Łubkowska; Małgorzata Paczyńska-Jędrycka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
More and more often specialized literature mentions the contemporarily relevant notion of the application of swimming as one of the therapeutic methods in modern medicine. The thesis reviews specialized literature and analyzes documents in order to demonstrate the significance of aquatic therapy and corrective swimming exercises as a corrective and therapeutic function in the treatment of postural deficits and scoliosis. As this article has a character of a review, its purpose is to attempt a concise synthesis of the knowledge concerning the impact of swimming as a sport on the development of the physiological spinal curvature, as well as to emphasize the significance of aquatic therapy and corrective swimming exercises in counterbalancing gravity and supporting the body weight and to demonstrate their health benefits.